Polyvinyl siloxane: novel material for external nasal splinting. Issue 1 (January 2016) - Jayakumar, N.K.; Rathnaprabhu, V.; Ramesh, S.; Parameswaran, A.
Abstract: External nasal splinting is performed routinely after nasal bone fracture reductions, osteotomies, and rhinoplasties. Materials commonly used include plaster of Paris (POP), thermoplastic splints, self-adhesive padded aluminium splints, and Orthoplast, among many others. The disadvantages of these materials are described in this paper, and polyvinyl siloxane is recommended as an effective and more readily available alternative material to counter these pitfalls.